Workplace observation of work stressors, catecholamines and musculoskeletal pain among male employees - Elfering, Achim; Grebner, Simone; Gerber, Hans; Semmer, Norbert K. (Scandinavian Journal of Work, Environment & Health, 2008)
' ' OBJECTIVES ': 'Prolonged activation of the sympathetic–adrenal medullary system during work and the lack of recovery after work may indicate a risk for musculoskeletal pain (ie, neck, shoulder, or low-back pain). This field study tested whether a high level of work stressors are associated with musculoskeletal pain and higher urinary norepinephrine excretion rates at work, after work, and on Sundays. ' ' METHODS ': 'Altogether 32 male employees working in adult education took part in a three-phase repeated-measures field study including workplace observation, self-report of musculoskeletal pain, and measurement of urinary catecholamine at work, in the evening after work, and at corresponding times on Sundays. ' ' RESULTS ': 'In univariate analyses, work stressors and workday levels of norepinephrine were significantly higher in the participants with high levels of musculoskeletal pain. Moreover, regressing workday norepinephrine excretion rates on predictor variables in the multilevel regression analysis showed a significant interaction between work stressors and musculoskeletal pain (P=0.011) with elevated excretion rates of norepinephrine in those exposed to a high level of work stressors and, at the same time, reporting higher levels of musculoskeletal pain. ' ' CONCLUSIONS ': 'High work stressors turned out to be associated with musculoskeletal pain and norepinephrine concentration in male employees. Increased activity of the sympathetic–adrenal medullary system seems to play an important role in work-related musculoskeletal pain.
Keywords: catecholamines; employee; male employee; man; musculoskeletal pain; norepinephrine; observation; recovery; unwinding; work stressor; workplace; workplace observation